José Mauricio Arruti (Editor) (2022); Panorama Quilombola - Yépez Montúfar, Jeanneth (2023)
The book "Panorama Quilombola do Brasil" edited by José Mauricio Arruti presents the work of 21 researchers committed to field work and the construction of political positions in favor of the recognition of the problems of the quilombola peoples. The book is divided into three parts: Quilombos y esfera pública, Educação Escolar Quilombola and Acesso dos Quilombos à Justiça. The book offers a critical perspective on research practices that sometimes suspend the history and richness of the transformations of populations that develop their existence in territories over which extractive capitalist interests loom. The book is a successful polyphony constructed by Afro-Brazilian researchers, as well as quilombolas and people of diverse ethnic affiliations in collaboration with the editor of the text.